Appropriate models for novel osteoporosis drug discovery and future perspectives. (2nd November 2015) - Gennari, Luigi; Rotatori, Stefano; Bianciardi, Simone; Gonnelli, Stefano; Nuti, Ranuccio; Merlotti, Daniela
Abstract : Introduction: Osteoporosis is a common skeletal disorder characterized by compromised bone strength and increased fracture risk. It is becoming a growing health-economic problem worldwide. Over the past two decades, there has been considerable progress in the availability of compounds with antiresorptive or anabolic activity on bone. However, existing therapeutic strategies still have limitations. Areas covered: In this review, the authors summarize past and current approaches for the development of antiresorptive and anabolic agents for osteoporosis together with their mechanisms of action. They also provide discussion on the application of new technologies for novel osteoporosis drug discovery. Expert opinion: Thanks to the recent advances in molecular biology over the past few years, novel therapeutic targets for antiresorptive or anabolic compounds have been discovered and several promising new drugs are in preclinical and clinical development. Despite these advances, the current understanding of the mechanisms regulating bone remodeling is far from complete, leaving significant drawbacks to the discovery and the clinical development of novel therapeutic agents. Hopefully, improvements in functional genomics and bioinformatics, along with new technological approaches such as RNA silencing, quantitative proteomics, metabolomics, and the use of mesenchymal stem cells, will address these issues and widen our options for treating several disorders of bone metabolism, including osteoporosis.